The Effect of Painting on Emotion, Anxiety and Blood Cell (CBC) Regulation in Children with Cancer - Maryam Pourkhoramshahi; Saeed Teymouri (Hamadan University of Medical Sciences, 2021)
Background and Objective: Diagnosis of cancer can cause significant psychological stress for the individuals and their family. Research shows social support has a positive and significant relationship with cellular immunity variables and some variables of blood cell count. Using tools such as painting, a child experiences all the issues of his life, tests and builds himself. The aim of this study was to evaluate the effectiveness of painting on cognitive regulation of emotion, anxiety and blood cells (CBC) in children aged 7 to 12 years with cancer. Material and Methods: This research was conducted for 2 months from May 2016. The research method was quasi-experimental with pre- and post-test design and a control group. Among 43 children aged 7 to 12 years with cancer who referred to Dr. Sheikh Hospital in Mashhad and volunteered to cooperate with the study, 30 were selected according to the entry and exit criteria and were randomly assigned to the experimental and control groups. Then painting and free therapy were performed in the subjects of the experimental group. Garnfsky et al. (2001) Emotion Regulation Questionnaire, Spence Children's Anxiety Scale (SCAS) and blood cell count test were used to collect data in pre- and post-test. Analysis of covariance was used to analyze the data. Results: Findings show that painting therapy is based on emotion regulation (F=293.8; P=0.001), anxiety (F=135.3; P=0.001), blood cell count test in WBC (F=13.2; P=0) and is effective in platelet count (F=152.77; P=0.001) in children with cancer. Performing painting therapy increases the components of emotion regulation and blood cell counting and reduces the components of anxiety. Conclusion: The overall goal of painting therapists is to enable clients to grow and transform in a healthy and safe environment by using painting tools. Therefore, in this program, sick children are given the opportunity to express their thoughts and feelings and communicate with others. According to the research findings, this approach can be used to work with children with cancer in counseling centers, hospitals and schools.